A new species of Eucalantica Busck (Lepidoptera, Yponomeutidae) poses potential concerns on blueberry industry in Mexico - Ruiz-Galvan, Isabel; Sohn, Jae-Cheon (Zootaxa, 2023)
A new species of Eucalantica, E. nestori n. sp. is reported on the basis of 13 type specimens collected from blueberry farms in Atzingo and Xoxonacatla, Puebla, Mexico. Habitus and genital features of the species are described and illustrated. Larval feeding habit of E. nestori n. sp. is demonstrated from field observations. Damage of the larvae was observed from the leaves, flowers and shoots of blueberries. Agricultural concerns involving E. nestori n. sp. are discussed.